Outcome of treatment in patients with recurrent respiratory papilomatosis in Kano - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background/Objectives:Respiratory papillomatosis (RP), which most often affects the larynx, is a relatively rare benign disease that can, however, have an aggressive clinical course. This study aimed to review the outcome of the patients treated for recurrent RP at Aminu Kano Teaching Hospital and the factors associated with the outcome.Materials and Methods:The records of patients managed for laryngeal papillomatosis at the Department of Otorhinolaryngology, Aminu Kano Teaching Hospital, Kano, Nigeria, over a period of 10 years between January 2004 and December 2013 were reviewed. Information obtained from the case files included demographic characteristics and clinical information. The data obtained were analysed using Statistical Package for Social Science version 16.Results:A total of 31 patients with recurrent RP were seen. Among these, 16 (51.6%) were males and 15 (48.4%) were females with sex ratio (M: F) of 1.1:1. The mean age was 11.7 years with standard deviation of ± 1.26. The main presenting symptoms were hoarseness in all patients and difficulty in breathing in 9 (29%). Patients who had the onset of symptoms between 6 and 10 years of age constituted the majority, 17 (54.8%). Only one patient had a solitary lesion on laryngoscopy, the majority had multiple papillomatous lesions, 30 (97.8%). Emergency tracheostomy was performed to relieve upper airway obstruction in 10 (32.3%). Twenty-seven of the patients constituting 87.1% had 1–3 surgical extirpations while 4 (12.9%) had surgery between 4 and 6 times. The voice outcome was mostly poor among the patients post-surgery, 27 (87.1%). Majority of the patients were lost to follow-up, 21 (67.7%), with 1 (3.2%) recorded death and 9 (29%) still on follow-up.Conclusion:There appears to be a limited success in the outcome of our patients managed for recurrent RP. However, early diagnosis and avoidance of tracheostomy where possible are factors that may improve the outcome.